Prognostic and Therapeutic Role of Vitamin D in COVID-19: Systematic Review and Meta-analysis - Dissanayake, Harsha Anuruddhika; de Silva, Nipun Lakshitha; Sumanatilleke, Manilka; de Silva, Sawanawadu Dilantha Neomal; Gamage, Kavinga Kalhari Kobawaka; Dematapitiya, Chinthana; Kuruppu, Daya Chandrani; Ranasinghe, Priyanga; Pathmanathan, Sivatharshya; Katulanda, Prasad (The journal of clinical endocrinology and metabolism, 2022)
Vitamin D deficiency/insufficiency may increase the susceptibility to coronavirus disease 2019 (COVID-19). We aimed to determine the association between vitamin D deficiency/insufficiency and susceptibility to COVID-19, its severity, mortality, and role of vitamin D in its treatment. We searched CINAHL, Cochrane library, EMBASE, PubMED, Scopus, and Web of Science up to May 30, 2021, for observational studies on association between vitamin D deficiency/insufficiency and susceptibility to COVID-19, severe disease, and death among adults, and, randomized controlled trials (RCTs) comparing vitamin D treatment against standard care or placebo, in improving severity or mortality among adults with COVID-19. Risk of bias was assessed using Newcastle-Ottawa scale for observational studies and AUB-KQ1 Cochrane tool for RCTs. Study-level data were analyzed using RevMan 5.3 and R (v4.1.0). Heterogeneity was determined by I2 and sources were explored through prespecified sensitivity analyses, subgroup analyses, and meta-regressions. Of 1877 search results, 76 studies satisfying eligibility criteria were included. Seventy-two observational studies were included in the meta-analysis (n = 1 976 099). Vitamin D deficiency/insufficiency increased the odds of developing COVID-19 (odds ratio [OR] 1.46; 95% CI, 1.28-1.65; P < 0.0001; I2 = 92%), severe disease (OR 1.90; 95% CI, 1.52-2.38; P < 0.0001; I2 = 81%), and death (OR 2.07; 95% CI, 1.28-3.35; P = 0.003; I2 = 73%). The 25-hydroxy vitamin D concentrations were lower in individuals with COVID-19 compared with controls (mean difference [MD] -3.85 ng/mL; 95% CI, -5.44 to -2.26; P ≤ 0.0001), in patients with severe COVID-19 compared with controls with nonsevere COVID-19 (MD -4.84 ng/mL; 95% CI, -7.32 to -2.35; P = 0.0001) and in nonsurvivors compared with survivors (MD -4.80 ng/mL; 95% CI, -7.89 to -1.71; P = 0.002). The association between vitamin D deficiency/insufficiency and death was insignificant when studies with high risk of bias or studies reporting unadjusted effect estimates were excluded. Risk of bias and heterogeneity were high across all analyses. Discrepancies in timing of vitamin D testing, definitions of severe COVID-19, and vitamin D deficiency/insufficiency partly explained the heterogeneity. Four RCTs were widely heterogeneous precluding meta-analysis. Multiple observational studies involving nearly 2 million adults suggest vitamin D deficiency/insufficiency increases susceptibility to COVID-19 and severe COVID-19, although with a high risk of bias and heterogeneity. Association with mortality was less robust. Heterogeneity in RCTs precluded their meta-analysis.